CONSTITUTIONAL REVIEW OF THE REGULATIONS REGARDING THE LAWYERS: AN EFFECTIVE WAY OF MAINTAINING AND STRENGTHENING THE PRESTIGE OF THE PROFESSION OF LAWYER - Valentina BĂRBĂȚEANU; Andrei MURARU (Challenges of the Knowledge Society)
The right to defense is fundamental in a democratic society, based on the rule of law. Its exercise requires skill, rigor, attention and an excellent knowledge of the legislation involved in each case. A truly professional defense can only be carried out by a genuine legal professional, by a lawyer who is a member of a bar recognized by law. Over the years, the regulation of the profession of lawyer has required legislative improvements to clarify and strengthen the legal status of lawyers as defenders of fundamental human rights. In this approach, the Constitutional Court played an important role, through its decisions on this issue. This paper aims to present the contribution that the constitutionality review had to the improvement of the regulations regarding lawyers.